The Influence of Anti–tumor Necrosis Factor Agents on Hemoglobin Levels of Patients with Inflammatory Bowel Disease. Issue 7 (July 2015) - Koutroubakis, Ioannis E.; Ramos-Rivers, Claudia; Regueiro, Miguel; Koutroumpakis, Efstratios; Click, Benjamin; Schwartz, Marc; Swoger, Jason; Baidoo, Leonard; Hashash, Jana G.; Barrie, Arthur; Dunn, Michael A.; Binion, David G.
Abstract : Background: Anti–tumor necrosis factor (TNF) agents are an important component of inflammatory bowel disease (IBD) treatment, but data on their influence on anemia, a frequent complication of IBD, are limited. The aim of this study was to evaluate the effect of anti-TNF agents on hemoglobin (Hb) levels in a large IBD cohort. Methods: Prospectively collected demographic, clinical, laboratory, and treatment data from IBD patients who started anti-TNF treatment at a tertiary referral center during the years 2010 to 2012 were analyzed. Follow-up data including disease activity scores (Harvey–Bradshaw index or ulcerative colitis activity index), quality of life scores (short IBD questionnaire) completed at each visit, and laboratory data were analyzed. Data from the year of anti-TNF initiation (yr 0) to the following year (yr 1) were compared. Results: A total of 430 IBD patients (324 with Crohn's disease, 51.6% females) started anti-TNF treatment. The prevalence of anemia and median Hb levels did not change between years 0 and 1. Median short IBD questionnaire was significantly improved at year 1 ( P = 0.002). IBD patients with anemia had significantly higher median Hb levels at year 1 compared with year 0 ( P = 0.0009). Hematopoietic response (increase of Hb ≥2 g/dL) was observed in only 33.6% of the 134 anemic IBD patients, despite iron replacement being administered in 126 anemic patients (oral, 77%). Improvement in Hb levels was independently significantly correlated with change of C-reactive protein levels ( P = 0.04) and immunomodulator use ( P = 0.03). Conclusions: Anemia remains a significant manifestation of IBD 1 year after treatment with anti-TNF agents. Abstract : Article first published online 30 April 2015.